(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Access to safe drinking water is very important issue at all level of life for maintaining good health and development. Water contamination by sewage waste is one of the most important causes of water pollution world-wide. Objectives: To detect the causative infectious agents from all hospitalized patients hailing from an area of simultaneous outbreak of jaundice and fever and also to highlight the importance of regular bacteriological tests of drinking water. Materials and Methods: This observational study was carried out among 1298 patients reported to CMH Chattogram between April 2018 to May 2018. For diagnosis, all relevant investigations were done following standard laboratory proceducers in CMH Chattogram, Armed Forces Institute of Pathology Dhaka and in ICDDR,B. Results: Out of 1298 admitted patients, 933(71.9%) patients had symptoms of acute viral hepatitis (AVH). IgM anti-HEV were found positive (100%) in 550 randomly selected hepatitis patients. From seropositive cases, 7 of the 10 random samples (70%) were found HEV-RNA positive by real time PCR. Co-infection of AVH with enteric fever was detected in 73(5.6%) patients. Only enteric fever was diagnosed in 150 (35.7%) high febrile cases. Water for bacteriological tests revealed thermos-tolerant E. coli immediately before and during the outbreak. Conclusion: Providing safe drinking water in a developing country is always a big issue. Contaminated drinking water can transmit deadly enteric pathogen that often causes a catastrophe of mass population. Only ensuring safe water distribution systems following WHO guidelines can minimize these sufferings. JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 7-9